قراءة النصوص العربية غير مشكولة والأخطاء الشائعة لدى طلبة قسم تعليم اللغة العربية بجامعة أنتساري الإسلامية الحكومية بنجرماسين - Darmawaty, Ridha (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2016)
The ability of students of Department of Arabic Language Education IAIN Antasari Banjarmasin in recite the nushus without a vowel in accordance with the rules nahwiyyah or sharfiyyah is imperative that demands urgent especially when students use the references in Arabic and when they teach in the field of practice at schools. However, there were frequent errors in certain functions, although the subject that supports the ability to read nushus not use harakat like nahwu, sharf, tarjamah, balagha, Maharat al lughawiah been programmed. Using quantitative descriptive study with an analysis of the value and errors that appear in the test results, the authors describe the general ability of students in reading nushus without a vowel is still classified as moderate with an average value of 73.23. As for the errors that frequently arise when giving a vowel of a word or phrase that serves as mudhaf ilaih, maf'ul bih, man'ut while the most frequent word that serves as khabar and mudhaf ilaih. The results of this study as information for teachers on students' ability to read nushus without a vowel and errors that often arise when the process is underway. This study is very significant in evaluating and improving learning outcomes as well as the deepening of designing materials based on the results of analysis errors. The authors recommended the bid in order to facilitate students in reading nushus without a vowel is by analysis of the functional structure are arranged in a sentence with a simple model.